PENGEMBANGAN E-MODUL INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR SISTEM EKSKRESI PADA MANUSIA - Syaiful, Syaiful; Salam, Urai; Maria, Haratua Tiur (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aimed to develop the interactive e-modules in improving learning outcomes of the excretory system in humans, furthermore it will be carried out effectively on the implementation of the products that have been developed. The method used in this research was Research and Development (R&D) by applying the ADDIE development model which consisted of five stages, namely Analysis, Design, Development, Implementation, and Evaluation with class VIII students of SMP Negeri 1 Hulu Gurung as research subjects. Interactive E-Modules were developed using the Flip Pdf application Corporate with an html application file format, html software can be accessed using a laptop/computer or Android. The course material was equipped with learning videos made using the Camtasia application and interactive quizzes made directly using the Filip pdf Corporate application. At the end of the learning activity there was a formative test that was made using a Google form whose link is linked in the Flip pdf Corporate application. Based on the results of the analysis, it showed that there was a significant difference in student learning outcomes before and after the use of interactive e-modules and based on the effect size test, a value of 1.10 is obtained, then compared with the comparison table, 1.10 is included in the Strong Effect criteria or gives effect or the interactive e-module have been developed give the strong effect.